Zhongguo ren rong yi xie cuo de zi : Li Wenqu zhu bian - Li, Wenqu (Beijing : Jiu zhou chu ban she, 2017)
$1!Ci'CU!L&!:}!C"'YJ']o!M"!:R!+5!:}!C"'YJ']o!M"!8}!`1!:R!+5!:}!C"'Xq'YJ!4\'\[!M"!:R!Oz!0#!9%!\k!3S'Q+!?b!+3!3"'CU!@W!:R!FB(BA$1!3b(BZ$1!M"'`;!<l!+8'XZ'Q,!3W'T4'Ms!:}!C"'YJ']o!+5!Gk!Gv!+5!MJ!0*!?M!+5!3S!0*KGa!M"!:R!5w'XO!+8!;I!3*!C''C-!<T!\<!3b!M"!5.!Ky!:R!+5!>+'L4!:R!+5!GH!Ky'XO!+5!^w!Ky!0d!5E!+5!Ky!2[!7y!5E!+8!31'\3!WD!3S'^MK3['`S!+8!\$!:R!+5!\$'XO!3S!X4!+8'<a!4)'YJ!R_'_9'C-'Po!F#']o'Xq!+3 s
This book consists of seven parts: easy-to-read words, easy-to-read polyphonic words, and misreading half-words. The book lists the words and words that are easy to read, confuse, incomprehensible, and indistinguishable in the order of letters A to Z, especially the ancient characters, weird words, derivatives, strange names, and unfamiliar names that are often encountered. , then classify, word-by-word, word-by-word decomposition, to help readers correct mistakes at any time.
Includes index
Keywords: Chinese language -- Writing; Chinese language -- Usage; Chinese character